Testosterone Administration Alters Hepatic Blood Flow Across Age: Systematic Review of Animal Experimental Studies - Nucci, Ricardo Aparecido Baptista; Tanasov, Valéria Simões; Krause Neto, Walter; de Souza, Romeu Rodrigues; Gama, Eliane Florencio (Journal of Morphological Sciences, 2018)
Testosterone levels decline gradually with advancing age. At this point, testosterone administration as a therapy has been largely used to improve different outcomes. However, testosterone induces dose-dependent negative effects on the structure and function of the liver across age. Therefore, the present study aimed to carry out a systematic review of the effects of testosterone administration on the hepatic structure of adult and aged animals. We have searched the PubMed, Google Scholar, Science Direct, Scielo and Lilacs databases for animal experimental studies on the effects of testosterone administration on the hepatic structure across age. After applying the inclusion and exclusion criteria, we included two articles in a systematic review and meta-analysis (regarding adult/aged rats). We have shown through a systematic review with meta-analysis that testosterone may cause chronic hepatic congestion. However, the present review had a small number of studies, which was considered a limitation. At this point, we encourage the development of more studies to elucidate the cellular and molecular mechanisms involved in hepatic injuries, as well as the hepatic metabolism of exogenous testosterone across age.
Keywords: aging; liver; hepatic structure; testosterone; androgenic anabolic steroids; review